Assessment of tillage erosion rates on steep slopes in northern Laos - Dupin, B.; Rouw, Anneke de; Phantahvong, K.B.; Valentin, Christian (Elsevier, 2009)
In the hills of south-east Asia shifting cultivation is developing towards more permanent cropping systems. In association with short fallow periods, fields suffer from weed pressure and this, in turn, leads to more frequent and deeper manual tillage. Due to steep slopes these operations induce tillage erosion. Measurements of such soil losses under on-farm conditions are still scarce. In this study tillage erosion was assessed and a predictive model of tillage erosion was established based on slope angle and contact cover, i.e. basal crop area and weed cover. The experiments were conducted in the Houay Pano, Northern Laos. The farmers cultivate annual crops in rotation with 1-3 year fallow periods without external inputs and using only hand tools. Tillage erosion was assessed using the tracer method across nine slope classes (0.30-1.10 m m1) for two crops, upland rice and Job's tears (Coix lacryma-jobi L.). Soil movement due to land preparation and weeding were assessed separately because different tools are used, a medium size hoe and a small curved hoe. A multivariate regression showed a highly significant relation (R2 = 0.83) between soil losses due to land preparation, slope gradient and contact cover. Predicting models of soil losses due to weeding were also highly significant (R2 = 0.79 for upland rice, R2 = 0.88 for Job's tears), confirming the importance of tillage erosion on steep slopes (4, 6 and 11 t ha1 year1 on slopes with gradients of 0.30, 0.60 and 0.90 m m1, respectively). Tillage erosion has increased exponentially over the last 40 years because of weed invasion associated with short fallow periods; the initially no-till system has changed into a system heavily dependent on tillage to control weeds and this greatly contributes to soil degradation.